Development of an Unmanned Aerial Vehicle (UAV) - Ong, Erwin Chong Xin (2017)
The Radio Control (RC) drones has been the center of attention in the last few years. Their simple design and easy to learn and control have led to more and more people into looking to aerial photography/videography and surveillances as a hobby as well as an interest. The purpose of this project is to look at the underlying technologies behind a drone and use the knowledge to build and develop a Raspberry Pi Powered Drone. It includes building the mainframe, developing the interface between the transmitter and receiver, implementing the flight controller, creating a model and running flight tests and simulations. The design of the drone may look simple, but understanding the technologies behind them requires different knowledge from a wide range of disciplines. The physics and aerodynamics of the drone are analyzed and a mathematical model is presented. Several sensors often used in a drone are looked at and mathematical equations are presented to process them. The accuracy of each sensor is then analyzed and an appropriate filter is used to improve the accuracy of the signals. Finally, a brief outline is given on the process of implementing the interface and controller onto a Raspberry Pi. The result shown that it is possible to develop a functional interface between the transmitter and receiver in the Raspberry Pi powered quadcopter.